2009
DOI: 10.1042/bst0370665
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of plant and archaeal viruses in bionanotechnology

Abstract: CPMV (cowpea mosaic virus), a plant virus, is a naturally occurring sphere-like nanoparticle, and is used as a synthon and/or template in bionanoscience. The virions formed by CPMV can be regarded as programmable nanobuilding blocks with a diameter of approximately 30 nm. A range of molecules have been attached to this viral nanoscaffold, yielding stable nanoparticles that display multiple copies of the desired molecule. It has been shown that, in addition to surface amine groups, surface carboxy groups are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Now, viruses are at the centre of discussions between evolutionists concerning their nature, their origin and their position in the tree of life [7,20,36,40,72,73]. Finally, they are also more and more involved in the design of new therapies (such as gene therapy) [74] or in the renewal of old ones (phage therapy) [75] and they have recently started to make their way in nanotechnology [76]. An aspect that has been neglected until now seems to be the more deliberate exploitation of their power as synthetic biologists.…”
Section: Resultsmentioning
confidence: 99%
“…Now, viruses are at the centre of discussions between evolutionists concerning their nature, their origin and their position in the tree of life [7,20,36,40,72,73]. Finally, they are also more and more involved in the design of new therapies (such as gene therapy) [74] or in the renewal of old ones (phage therapy) [75] and they have recently started to make their way in nanotechnology [76]. An aspect that has been neglected until now seems to be the more deliberate exploitation of their power as synthetic biologists.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13] It contains one positive-sense single-stranded RNA of ∼6395 nucleotides carrying the genetic information, 14 embedded within a protein coat of ∼2130 identical, helically arranged monomers. This rigid rod-like nucleoprotein structure -the virion -of about 300 × 18 nm encloses a longitudinal channel 4 nm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, an archaeal virus has never been evaluated in vivo , but the potential for their use as nano‐vector platforms has been proposed (Steinmetz et al . ; Evans ; Uldahl and Peng ) and recently, an in vitro study investigating SMV1 and its interaction with mammalian cells provided promising results (Uldahl et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…As with plant viruses and bacteriophages, SMV1 should not be pathogenic to humans or animals. To our knowledge, an archaeal virus has never been evaluated in vivo, but the potential for their use as nano-vector platforms has been proposed (Steinmetz et al 2008;Evans 2009;Uldahl and Peng 2013) and recently, an in vitro study investigating SMV1 and its interaction with mammalian cells provided promising results (Uldahl et al 2016b). In this study, SMV1 was shown to be efficiently internalized by both human endothelial cells of brain and umbelical vein origin without any detrimental effect on cell morphology, plasma membrane and mitochondrial functionality (Uldahl, Wu, Hall, Papathanasiou, Peng, and Moghimi 2016b), thus indicating SMV1 as a promising therapeutic nano-vector.…”
Section: Introductionmentioning
confidence: 99%